2019
DOI: 10.1186/s12877-019-1123-1
|View full text |Cite
|
Sign up to set email alerts
|

Cementless short-stem total hip arthroplasty in the elderly patient - is it a safe option?: a prospective multicentre observational study

Abstract: Background Due to its bone preserving philosophy, short-stem total hip arthroplasty (THA) has primarily been recommended for young and active patients. However, there may be benefits for elderly patients given a less invasive operative technique due to the short curved implant design. The purpose of this study was to compare the clinical and radiological outcomes as well as perioperative complications of a calcar-guided short stem between a young (< 60 years) and a geriatric (> 75 years) populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 51 publications
2
48
0
1
Order By: Relevance
“…Examining the Optimys short stem (Mathys, Bettlach, Switzerland), Gkagkalis et al demonstrated bone resorption in up to 15%, Values are given as mean and standard deviation (SD). None of the investigated parameters showed a statistical significant influence on subsidence at the latest follow-up, indicated by a p value > 0.05 occurring mainly in the proximal zones 1, 2, and 7 at a mean follow-up of 49 months, However, only 1.7% of the investigated implants revealed radiolucent lines of less than 2 mm [40]. Using an ultra-short, metaphyseal-fitting femoral component (Proxima, DePuy, Leeds, UK), Kim et al found no radiolucent lines at all at a mean follow-up of 7.9 years [41].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Examining the Optimys short stem (Mathys, Bettlach, Switzerland), Gkagkalis et al demonstrated bone resorption in up to 15%, Values are given as mean and standard deviation (SD). None of the investigated parameters showed a statistical significant influence on subsidence at the latest follow-up, indicated by a p value > 0.05 occurring mainly in the proximal zones 1, 2, and 7 at a mean follow-up of 49 months, However, only 1.7% of the investigated implants revealed radiolucent lines of less than 2 mm [40]. Using an ultra-short, metaphyseal-fitting femoral component (Proxima, DePuy, Leeds, UK), Kim et al found no radiolucent lines at all at a mean follow-up of 7.9 years [41].…”
Section: Discussionmentioning
confidence: 79%
“…Regarding radiolucent lines, the investigated short stem demonstrated a high rate of periprosthetic radiolucency compared to other short stem designs. Examining the Optimys short stem (Mathys, Bettlach, Switzerland), Gkagkalis et al demonstrated bone resorption in up to 15%, occurring mainly in the proximal zones 1, 2, and 7 at a mean follow-up of 49 months, However, only 1.7% of the investigated implants revealed radiolucent lines of less than 2 mm [ 40 ]. Using an ultra-short, metaphyseal-fitting femoral component (Proxima, DePuy, Leeds, UK), Kim et al found no radiolucent lines at all at a mean follow-up of 7.9 years [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 , 23 , 24 , 25 ] Among the main risks for periprosthetic fractures in cementless THA, higher patient age has been identified. [ 21 ] In contrast, cemented femoral stems have been shown to minimize the risk of early complications with excellent long-term survivorship. [ 5 , 26 , 27 ] Therefore, cemented THA was predominantly used in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, Europe and many hospital in China, DAA THA was mainly performed in supine position with short femoral stem, which required special operation bed and high cost [9,10]. There was not special operation bed in our Hospital.…”
Section: Introductionmentioning
confidence: 92%